PENGARUH EKUITAS MEREK TERHADAP LOYALITAS PEMBELIAN TEH BOTOL SOSRO PADA MAHASISWA UNIVERSITAS JAMBI PROGRAM REGULER - Fransisca . Yulianti (Konsentrasi Manajemen Pemasaran Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2017)
The purpose of this research: 1) explaining the effect of brand equity that consists of brand awarness, quality perception, brand association, and brand loyalty on the BotleSosro Tea (BST),and (2) explaining purchasing loyalty that shoul be managed at retail level. Sample was chosen from regular students at Jambi University that purchaseBST everyday. Based on research results, brand awarness (X1), quality perception (X2), brand association (X3), and brand loyalty (X4) simultaneously infulenced significantly on purchase loyalty, it shows by F 25,7%. Furhermore, partially the effect of X1, X2, dan X4 are significant, otherwise the influence of X3 is not significant. This finding indicates that 25, 7 percent that could be explained by the predictor ant others 74, 3, % is exlained by other predictors. Hence, purchusening loyaltiy should be managed rigorously to make customer be more aware about the TBS brand. Keywords: brand awarness, quality perception, brand association, and brand loyalty, purchase loyalty, Botle Sosro Tea